ANALISIS KINERJA PEGAWAI BERDASARKAN KOMPETENSI, BUDAYA ORGANISASI DAN DISIPLIN KERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA SUNGAI PENUH: IRVAN ZULHAKIM, S.STP - IRVAN ZULHAKIM (JURNAL ADMINISTRASI NUSANTARA, 2021)
This study aims to determine the effect of independent variables on the dependent variable. The object of this research is the Employees of the Full River City Human Resources and Human Resources Development Agency (BKPSDM). The number of samples in this study were 98 respondents. The analysis technique used is multiple linear regression. The research results obtained based on the partial test (t test) obtained: (a) There is a positive and significant effect of competence on employee performance. (b) There is a positive and significant influence of organizational culture on employee performance. c) There is a positive and significant influence of work discipline on employee performance. The results of the study simultaneously showed that competence, organizational culture and work discipline had a positive and significant effect on employee performance. And based on the coefficient of determination test (R2) the value is 0.624 or 62.4%, this shows that the percentage of the contribution of the independent variable competency, organizational culture and work discipline to the dependent variable of employee performance is 0.624 or 62.4%. While the remaining 37.6% is influenced by other variables outside this study.